2022
DOI: 10.1186/s40814-022-01099-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing national audit through addressing the quality improvement capabilities of feedback recipients: a multi-phase intervention development study

Abstract: Background National audits are a common, but variably effective, intervention to improve services. This study aimed to design an intervention to increase the effectiveness of national audit. Methods We used interviews, documentary analysis, observations, co-design and stakeholder engagement methods. The intervention was described in an intervention manual and illustrated using a logic model. Phase 1 described the current hospital response to a nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…By describing practices in the organizational response, this paper aims to support feedback providers and quality improvement leads to consider influences upon the implementation of these improvement practices; for example, the barriers and facilitators to clinical leads engaging stakeholders or exploring influences upon clinical performance. Important barriers and facilitator to implementation included how feedback recipients differentiate the approach from current practice, how they work with others to organize themselves to participate in a new practice and how they buy-in to the new approach 7 . Theory-informed co-design work identified that implementation may involve demonstration of the practices, supporting feedback recipients to plan how and when to carry them out and a credible source communicating in favour of the practices 7 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…By describing practices in the organizational response, this paper aims to support feedback providers and quality improvement leads to consider influences upon the implementation of these improvement practices; for example, the barriers and facilitators to clinical leads engaging stakeholders or exploring influences upon clinical performance. Important barriers and facilitator to implementation included how feedback recipients differentiate the approach from current practice, how they work with others to organize themselves to participate in a new practice and how they buy-in to the new approach 7 . Theory-informed co-design work identified that implementation may involve demonstration of the practices, supporting feedback recipients to plan how and when to carry them out and a credible source communicating in favour of the practices 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Important barriers and facilitator to implementation included how feedback recipients differentiate the approach from current practice, how they work with others to organize themselves to participate in a new practice and how they buy-in to the new approach 7 . Theory-informed co-design work identified that implementation may involve demonstration of the practices, supporting feedback recipients to plan how and when to carry them out and a credible source communicating in favour of the practices 7 . Creating both the physical opportunity (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations